Gerakan Percepatan Penurunan Stunting Terkait Kelainan Kulit pada Ibu dan Anak - Satya Wydya Yenny; Dwi Sabtika Julia; Resya I Noer; Nellia Fonna; Muhammad Fadil; Muhammad Zidan Amriza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Stunting is one of the most common health problems in the world and is ranked fifth in Indonesia. Stunting, which is still high in Solok Regency, is one of the problems in West Sumatra Province. To reduce stunting, the Venereology Dermatology Service Team conducted counselling to health extension workers and cadres of the Family Welfare Movement (PKK) regarding malnutrition, parenting, sanitation, and infectious and non-infectious skin diseases. This service aimed to carry out outreach activities to increase understanding of the acceleration of stunting reduction. The implementation method was outreach to 64 health workers and PKK cadres. Advocacy was also carried out at the Kominfo service and the Solok District Health Office. The results obtained before the socialization activity revealed that 61% of respondent’s knowledge was still low, whereas 66% increased after the activity. Respondent behaviour was obtained by 92% of respondents who had behaved well; after the activity was obtained, it became 98%. The excellent attitude of respondents toward preventing stunting before being given counselling was 73%, increasing to 91% after counselling. Skin disorders in pregnant women associated with giving birth to stunted children include eczema (51%) and skin disorders in stunted children, namely scabies (49%).